A comparative evaluation of the performance and emission characteristics of compression ignition engine using water diesel emulsion as fuel - Murali, V. (2006)
The basic intent of present work is to evaluate the potential of using water diesel emulsion for a compression ignition engine. A comparative analysis of the performance and emission characteristics of the engine has been made with respect to diesel and water diesel emulsion as fuels. A multicylinder diesel engine was run on water diesel emulsion and diesel at a constant speed of 2400rpm under variable load conditions and at 13-mode test cycle. Emulsions of 5, 10, 15 and 20 percent by volume of water in diesel were used. The results indicate that the addition of water in the form of emulsion improve the combustion efficiency. The optimum percentage of water in emulsion based on specific fuel consumption and emission characteristics compared to that of diesel fuel operation was 15%.